A snicker of magic [compact disc, unabridged] - Lloyd, Natalie (Scholastic Audio, 2013)
The Pickles are new to Midnight Gulch, Tennessee, a town which legend says was once magic--but Felicity is convinced the magic is still there, and with the help of her new friend Jonah the Beedle she hopes to bring the magic back.